Stone & steel public works at work, 2001-2007 : President Gloria Macapagal Arroyo's infrastructure program. (Department of Public Works and Highways, 2008)
"Stone and Steel is a visual directory of the roads, bridges and other infrastructure projects completed from 2001 to 2007, under the direction and guidance of President Gloria Macapagal Arroyo."--Book jacket.